ANALISIS BUKU TEKS GEOGRAFI SMA KELAS XII PADA MATERI POLA KERUANGAN DESA DAN KOTA DALAM BUKU SEKOLAH ELEKTRONIK TERBITAN DEPARTEMEN PENDIDIKAN NASIONAL - Amin, Saiful (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
The purpose of research is to know the level of the suitability of the content to the curriculum,Â the truth of concept, the truth of language, truth and the function of media images contained in the textbook BSE Geography class XII. This study is a content analysis using the document as an object. The design of research using content analysis techniques to describe objectively, systematically, and communicative with using a set of procedures to draw conclusions from a text book. The population in this study are all Geography Document class XII DIKNAS publications that have been circulating. Determination of sample use purposive sampling, a like BSE, entitled â€Geografi untuk Kelas XII SMA/MAâ€, by Eny Anjayani and Tri Haryanto. The results showed that there are some of the content of the material that is not in accordance withÂ the indicators, the truth of concept (the concept of undefined and a concrete concept) is still wrong, truth in language textbook BSE Geography is still wrong, and media images that are used in the textbook still does not work. It is recommended when using text books, teachers should first examine whether the content of textbooks is already fit for use or left things out that need to be improved, both in terms of curricular as well as in terms of the concept of truth. If found shortcomings or mistakes should be corrected first before delivered during learning. In addition, the author should revise the textbooks BSE Geography class XII mainly in conformity with the curriculum content, the truth of concept, the truth of language, and the function of drawing media.Keywords: text analysis, BSE, pattern of the Rural and Urban.Â